2023
DOI: 10.1099/acmi.0.000457
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 cavitary lung lesion due to Aspergillus flavus and Enterobacter cloacae in a patient suffering from COVID-19 pneumonia – a case report

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has manifested as a multifaceted paradigm but has primarily affected the respiratory system. Though a rare sequela after-COVID-19, we present a case of cavitary lung lesion in an adult patient, which manifested with common symptoms such as fever, cough and dyspnoea during the post-COVID-19 recovery period. Aspergillus flavus and Enterobacter cloacae were found to be the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The subsequent development of invasive pulmonary aspergillosis underscores the importance of vigilance in observing severe COVID-19 pneumonia patients for potential opportunistic infections, particularly with prolonged corticosteroid therapy. Similarly, Rajpal et al's study [33] reported a rare sequela of pulmonary cavitation following COVID-19 recovery in an adult patient, with cavitary lung lesions attributed to Aspergillus flavus and Enterobacter cloacae. This highlights the possibility of fungal and bacterial coinfections in post-COVID-19 recovery, emphasizing the need for prompt recognition and appropriate treatment to prevent further morbidity and mortality.…”
Section: Discussion and A Brief Review Of The Literaturementioning
confidence: 85%
“…The subsequent development of invasive pulmonary aspergillosis underscores the importance of vigilance in observing severe COVID-19 pneumonia patients for potential opportunistic infections, particularly with prolonged corticosteroid therapy. Similarly, Rajpal et al's study [33] reported a rare sequela of pulmonary cavitation following COVID-19 recovery in an adult patient, with cavitary lung lesions attributed to Aspergillus flavus and Enterobacter cloacae. This highlights the possibility of fungal and bacterial coinfections in post-COVID-19 recovery, emphasizing the need for prompt recognition and appropriate treatment to prevent further morbidity and mortality.…”
Section: Discussion and A Brief Review Of The Literaturementioning
confidence: 85%